A finite element study on the effects of follower load on the continuous biomechanical responses of subaxial cervical spine. (June 2022) - Sun, Zhongwei; Lu, Teng; Li, Jialiang; Liu, Jiantao; Hu, Yuanbin; Mi, Changwen
Abstract: In spine biomechanics, follower loads are used to mimic the in vivo muscle forces acting on a human spine. However, the effects of the follower load on the continuous biomechanical responses of the subaxial cervical spines (C2-T1) have not been systematically clarified. This study aims at investigating the follower load effects on the continuous biomechanical responses of C2-T1. A nonlinear finite element model is reconstructed and validated for C2-T1. Six levels follower loads are considered along the follower load path that is optimized through a novel range of motion-based method. A moment up to 2 Nm is subsequently superimposed to produce motions in three anatomical planes. The continuous biomechanical responses, including the range of motion, facet joint force, intradiscal pressure and flexibility are evaluated for each motion segment. In the sagittal plane, the change of the overall range of motion arising from the follower loads is less than 6%. In the other two anatomical planes, both the magnitude and shape of the rotation-moment curves change with follower loads. At the neutral position, over 50% decrease in flexibility occurs as the follower load increases from zero to 250 N. In all three anatomical planes, over 50% and 30% decreases in flexibility occur in the first 0.5 Nm for small (≤100 N) and large (≥150 N) follower loads, respectively. Moreover, follower loads tend to increase both the facet joint forces and the intradiscal pressures. The shape of the intradiscal pressure-moment curves changes from nonlinear to roughly linear with increased follower load, especially in the coronal and transverse planes. The results obtained in this work provide a comprehensive understanding on the effects of follower load on the continuous biomechanical responses of the C2-T1. Graphical abstract: Image 1 Highlights: The follower load path is optimized through a novel Rom-based method. A nonlinear logarithmic function is proposed to fit the rotation-moment data. The continuous biomechanical responses of the cervical spine were investigated. The follower load increases both the facet joint forces and intradiscal pressures. The follower load impacts the shape of Rom-moment curves in all anatomical planes.